The role of the African organic intellectuals in the (re) centering of African cultural values and practices: towards the Sankofa paradigm - Tondi, Pakiso (Gender and Behaviour, 2017)
The aim of this paper is to identify challenges confronting the post-colonial Africa in the 21st century and the context of globalisation processes, and to locate the role of the African organic intelligentsia in reclamation and revitalization processes of the African culture, values and practices over against the domination of the European perspective and mind set. Here the main task is to highlight the significance of the appropriation of indigenous cultural values, traditions, knowledges and innovations in the reconstruction and socio-political and economic development of African communities.
Published Article